The Relationship Between Key Financial Ratios To The Revenue Growth And Financial Performance Benchmarking Analysis Of Oil & Gas Companies Listed In The Indonesian Stock Exchange - Fakhreza Samudera Budi; Erman Sumirat (UniSadhuGuna Business School, 2024)
The global oil and gas sector, a crucial driver of economic vitality, remains a focal point for investors navigating the dynamic energy market. According to the Handbook of Energy and Economic Statistics of Indonesia, the oil and gas industry constitutes a significant portion, approximately 43.5%, of the country's energy mix in 2022, equivalent to about 797 million barrels of oil equivalent (BoE). Projections from Indonesia’s Long-Term Strategy for Low Carbon and Climate Resilience (LTS-LCCR) 2050 anticipate an increase to 1.4 billion BoE in 2050, even under the strictest emission scenarios. Given the pivotal role of oil and gas in Indonesia's energy landscape, it is imperative to examine investor interest in companies within this industry. Regarding the oil & gas companies in the Indonesian Stock Exchange (IDX), investors' attention has been drawn to only a few stocks in particular due to the attractiveness of profitable prospects in the oil and gas sector, which brings up the question: do these “popular” oil and stocks really perform admirably financially? Overall, this research uses the quantitative method. This research has the purpose to identify and analyze the financial ratios that have a significant impact on the revenue growth of Indonesian oil & gas companies, to determine which Indonesian oil & gas companies with significant ratios exhibit high potential and possess a high market capitalization, to identify Indonesian oil & gas companies with significant ratios that demonstrate high potential and have a low market capitalization, to evaluate Indonesian oil & gas companies with significant ratios that exhibit low potential but possess a high market capitalization, and to compare the financial performance of the high potential Indonesian oil & gas companies with highly reputable oil & gas companies that are not listed on the Indonesian Stock Exchange. To complete the first objective, this research uses regression analysis, which resulted in Asset Turnover and Assets Growth as the significant ratios to the Revenue Growth. Using these significant ratios to measure the potential, the High Potential – High Market Cap category included AKRA, RAJA, ELSA, and HITS while in the High Potential – Low Market Cap category, this research has found out KOPI is qualified into this category. In the Low Potential – High Market Cap category, TAMU and BULL are included. Lastly, when compared to worldwide industry leaders, the IDX-listed oil & gas companies which are marked as High Potential have found some interesting findings: AKRA have much better Asset Turnover ratio than industry leaders, ELSA’s Assets Growth are observably better than Halliburton and Schlumberger, and HITS’ profitability (Gross Profit Margin) is still better than the spectacularly growing Pertamina International Shipping.